2017
DOI: 10.1111/codi.13779
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for constipation: systematic review and practice recommendations

Abstract: Aim To assess the outcomes of colectomy in adults with chronic constipation (CC).Method Standardised methods and reporting of benefits and harms were used for all CapaCiTY reviews that closely adhered to PRISMA 2016 guidance. Main conclusions were presented as summary evidence statements (SES) with a summative Oxford Centre for EvidenceBased Medicine (2009) level.Results Forty articles were identified, providing data on outcomes in 2045 patients. Evidence was derived almost exclusively from observational studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 55 publications
2
56
0
3
Order By: Relevance
“…It therefore has the potential to become a more attractive alternative, when more data become available on efficacy and complications. Surgical procedures for chronic refractory constipation include total colectomy with ileorectal anastomosis and subtotal colectomy with ileosigmoid/colorectal anastomosis . Mean success rate for these interventions is reported to be high, around 89% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore has the potential to become a more attractive alternative, when more data become available on efficacy and complications. Surgical procedures for chronic refractory constipation include total colectomy with ileorectal anastomosis and subtotal colectomy with ileosigmoid/colorectal anastomosis . Mean success rate for these interventions is reported to be high, around 89% .…”
Section: Discussionmentioning
confidence: 99%
“…When all conservative measures fail, surgical treatments such as appendicostomy, ileostomy with colonic exclusion, or segmental or total colectomy are considered . Previous reports demonstrate variable efficacy of these surgical treatment entities, and morbidity of these procedures is high . Less invasive and potentially reversible procedures such as sacral neuromodulation and tibial nerve stimulation have been disappointing with respect to efficacy .…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of benefit of colonic resections is weak and almost exclusively derived from observational studies. A systematic review of 40 articles, providing outcome data in 2045 patients, reported that colectomy may benefit some patients with FC but at the cost of substantial short-and long-term morbidity [54]. Complications occur in 25% of patients.…”
Section: Colonic Surgerymentioning
confidence: 99%
“…Many, if not nearly all, patients with STC have abdominal pain, and many have bloating. If these are the main symptoms, then colectomy is unlikely to help since surgery if anything worsens rather than improves these symptoms accounting for much of the postinterventional health utilization observed by Dudekula et al . Prior to colectomy, a temporary loop ileostomy may help ascertain whether symptoms emanate from the small intestine or colon.…”
Section: The Available Treatment Options For Refractory Constipationmentioning
confidence: 99%
“…How does PEC compare with surgical interventions for constipation? A systematic review of the latter suggested that 86% of patients were satisfied after surgery, 20%‐30% had complications, and 13% required re‐operation. By comparison, 30% of patients have complications after the Malone procedure …”
Section: The Available Treatment Options For Refractory Constipationmentioning
confidence: 99%